Balanced nutrition education for adolescents: Pre-post test approach to increase awareness of healthy diets in disaster-prone areas - Febiani Riskika; Ummu Aiman; Aldiza Intan Randani; Nurulfuadi; Try Nur Ekawati Lukman; Linda Ayu Rizka Putri (LPPM Politeknik Sandi Karsa, 2025)
Adolescents are vulnerable to nutritional problems, especially in disaster-prone areas with limited access to nutritious food. Sigi District, Central Sulawesi, was severely affected by the 2018 earthquake and liquefaction, which disrupted food security and increased instant food consumption. This study aimed to evaluate the effectiveness of balanced nutrition education using a pre-test and post-test approach in improving students’ knowledge of healthy eating at SMK 1 Sigi. The intervention involved 30 students who received lectures and leaflets on the Balanced Nutrition Guidelines. Knowledge was assessed through pre- and post-tests, and differences were analyzed statistically. Results indicated a significant increase in mean knowledge scores from 37.31 ± 15.89 to 65.77 ± 21.20 (p < 0.05). The proportion of students in the poor category decreased from 93.33% to 30%, while those in the fair and reasonable categories increased substantially. These findings highlight that simple educational interventions can enhance adolescents’ nutritional awareness in disaster-affected areas. Therefore, balanced nutrition education should be integrated into school health programs as a sustainable preventive strategy